New-Onset Nephrotic Syndrome in a Child Associated With COVID-19 Infection - Shah, Siddharth A.; Carter, Helen P. (Frontiers in Pediatrics, 2020)
Introduction: The COVID-19 outbreak has become a worldwide public health emergency. The renal histopathological features of acute tubular necrosis or thrombotic microangiopathy have been previously reported in adults with severe COVID-19 infections. In children, the renal manifestations associated with COVID-19 disease are not widely reported. Here, we describe a case report of a child with new-onset nephrotic syndrome associated with COVID-19 infection. Case Presentation: An eight-year-old boy with no previous significant medical history presented with bilateral eyelid and facial swelling soon after his parents were diagnosed with COVID-19 infection. He had diarrhea but no fever or shortness of breath. One week after the onset of swelling, the boy tested positive for the COVID-19 virus. Based on clinical findings of significant proteinuria (urine protein and creatinine ratio of 11.4), hypoalbuminemia (serum albumin of 2 g/dL), and hypercholesterolemia (total cholesterol of 384 mg/dL), he was diagnosed with nephrotic syndrome. He responded well to standard-dose prednisone treatment for nephrotic syndrome. One week after starting prednisone treatment, he went into clinical remission. Lymphopenia continued to be present for four weeks after the onset of symptoms. There were no complications related to clot formation or secondary infections with this presentation. Conclusion: COVID-19 can be associated with new-onset nephrotic syndrome in children. The patient responded well to the standard-dose prednisone treatment that is typically used for new-onset nephrotic syndrome.